Evaluating the flow regulating effects of ecosystems in the Mekong and Volta river basins - Lacombe, Guillaume; McCartney, Matthew P. (International Water Management Institute, 2016)
By altering evapotranspiration and influencing how water is routed and stored in a basin, natural and agrarian ecosystems affect river flow. To quantify the impact of ecosystems on streamflow in two large river basins in Asia and Africa, simple statistical relationships were calculated, enabling flow characteristics to be ascertained from basic catchment features. This approach allows the impact of specified land-use change on streamflow to be determined. For example, it shows that extending paddy areas in the Mekong River Basin reduces downstream low flows, while conversion of forests to crops increases the magnitude of downstream floods in the Volta River Basin. The approach could assist river basin planners to better account for flow-related ecosystem services.